Effect of the flyer material on the interface phenomena in aluminium and copper explosive welds - Carvalho, Gustavo (2019)
The effect of physical and mechanical properties of three different flyers on the interface phenomena of partially overlapped explosive welds, using the same base plate material, was studied. Flyers of Copper Cu-DHP and aluminium alloy 6082 (tempers T6 and O) were welded to AA6082-T6 base plates. The morphology of the weld interface is strongly influenced by the physical and mechanical properties of the flyer. In the interface of the aluminium welds, the use of a flyer of lower hardness and yield strength than the base plate results in asymmetrical waves, with bigger amplitude and smaller wavelength than the weld series of similar temper, and higher mechanical properties. The copper-aluminium welds presented flat interfaces, mainly because of the significant differences in melting temperature and density between the copper flyer and the aluminium base plate. Considering these results and analysing several dissimilar welds carried out by other authors it was found that when the product of density and melting temperature ratios between the flyer and the base plate exceeds a certain value, there is no formation of waves at the interface of the metals. Furthermore, for the Cu-Al welds, the CuAl2 (theta) intermetallic phase was formed on the bond zone.